Ethyl 4-nitrophenylacetate - Li, Ji (International Union of Crystallography, 2008)
In the asymmetric unit of the title compound, C(10)H(11)NO(4), there are two crystallographically independent molecules, which are connected via a C—H⋯O hydrogen bond. The crystal structure is stabilized by this hydrogen bond together with an N—O⋯π contact [O⋯Cg 3.297 (5) Å; Cg is the centroid of one of the benzene rings].